Struktur dan Komposisi Hutan Mangrove di Negeri Kamarian Kecamatan Kairatu Kabupaten Seram Bagian Barat, Maluku - Creysmen Ginesio Pentury; Irwanto, Irwanto; Moda Talaohu (Yayasan Literasi Sains Indonesia, 2025)
Mangrove forests represent one of the most ecologically and economically significant coastal ecosystems. Ecologically, well-structured mangrove vegetation functions as a natural buffer protecting coastlines from erosion, saltwater intrusion, and tidal wave impacts. This research aims to determine the structure and composition of mangrove forests and identify mangrove growth habitats in Kamarian. The vegetation analysis employed the line plot method with measurement plots of 20 m × 20 m for all growth stages (seedling, sapling, and tree), consisting of two blocks: Block A with 36 plots covering 1.44 ha, and Block B with 25 plots covering 1.00 ha. Results indicate that mangrove forests in Kamarian can be classified into four strata according to tree height: Stratum A (20-28 m), Stratum B (5-20 m), Stratum C (1-5 m), and Stratum D (0-1 m). Tree diameter variations ranged from 10 to 148 cm, with heights reaching 5-28 meters. Block A contained four mangrove species: Sonneratia alba, Aegiceras corniculatum, Rhizophora apiculata, and Sonneratia caseolaris, while Block B contained only two species: Aegiceras corniculatum and Sonneratia alba. The Shannon-Wiener species diversity index for all growth stages in Kamarian's mangrove forests ranged from 0.20 to 0.81, categorized as low diversity.